Petrographic and Geotechnical Characterization of Granites from Karay (Eastern Chad) for Their Use in Civil Engineering - Zagalo, Al-Hadj Hamid; Hamid, Adelkerim Hassan; Rochette, Pierre; Konaté, Moussa (European Journal of Applied Sciences, 2022)
Chad is in need of huge amount of aggregates, the most used materials, for its building and road construction. It is necessary to evaluate the geotechnical properties of the different types of rock outcropping in this country. This paper is focused on the petrography and geotechnical characteristics of granites from Karay (East Chad) for their use in civil engineering. The study area is located in the eastern Chad at about 50 km south to the town of Oumhadjer. The rocks that outcrop there form an isolated relief within a vast expanse of sand forming an inselberg. This relief is made up of fine, medium to coarse grained monzogranite cropping out as blocks and slabs, exposed to surface conditions (temperatures, waters and winds) that sometime transformed the micas and feldspars into clay. Microscopic description of thin sections of rock shows that they display a medium grained texture and are composed of quartz (32.8%), alkali feldspar (24.7%), plagioclase (21.4%), biotite (10.4%), muscovite (6.8 %) and opaques (3.7%). The geotechnical data showed that aggregates from the above rocks display Los-Angeles coefficient varying between 20.50 and 39.70% with an average of 29.60% and a Microdeval coefficient of comprised between 6.9 and 12.6 % with an average of 9.4%. These results indicate that the study materials can be used for civil engineering works. The correlation between the petrographic and geotechnical results indicates that the size of the grains, their arrangement (texture) and the mineralogical composition of rocks influence the geotechnical behavior of the aggrgates.